A risk assessment based approach to the management of acute poisoning. Issue 5 (20th April 2006) - Daly, F F S; Little, M; Murray, L
Abstract : Early assessment and management of poisoning constitutes a core emergency medicine competency. Medical and psychiatric emergencies coexist; the acute poisoning is a dynamic medical illness that represents an acute exacerbation of a chronic underlying psychosocial disorder. The emergency physician must use an approach that ensures early decisions address potentially time critical interventions, while allowing management to be tailored to the individual patient's needs in that particular medical setting. This article outlines a rationale approach to the management of the poisoned patient that emphasises the importance of early risk assessment. Ideally, this approach should be used in the setting of a health system designed to optimise the medical and psychosocial care of the poisoned patient.